The efficacy and efforts of interest groups in post elections policy formation - Gil S. Epstein; Yosef Mealem; Shmuel Nitzan (Center for Economic Studies and ifo Institute (CESifo), 2012)
This paper presents a new model of interest groups and policy formation in the legislature. In our setting, the already given party ideological predispositions and power distribution determine the expected policy outcome. Our analysis applies to the case of un-enforced or enforced party discipline as well as to two-party and multi-party (proportional representation) electoral systems. The interest groups' objective is to influence the outcome in their favor by engaging in a contest that determines the final decision in the legislature. Our first result clarifies how the success of an interest group hinges on the dominance of its ideologically closer party and, in general, the coalition/opposition blocks of parties under un-enforced party or coalition/opposition discipline. Such dominance is defined in terms of ideological inclination weighted by power. Our second result clarifies how the success of an interest group hinges on the dominance of its ideology in the ruling coalition (party) in a majoritarian system with enforced coalition (party) discipline. We then clarify under what condition an interest group prefers to direct its lobbying efforts to two parties or the two coalition and opposition blocks of parties under un-enforced discipline rather than to the members of the ruling coalition (party) under enforced discipline. The lobbying efforts under un-enforced and enforced party discipline are also compared. Finally, we clarify the effect of ideological predispositions and power on the efforts of the interest groups.
Keywords: D70; D72; D74; D78; 330; policy formation; political parties; ideological predispositions; electoral power; post-elections lobbying; enforced party discipline